DETERMINAN STRESS PADA DOKTER YANG MENANGANI PASIEN COVID 19 DI RUMAH SAKIT MURNI TEGUH - Purwana, Purwana; Rochadi, R. Kintoko; Sitorus, Mido Ester J.; Nababan, Donal; Silitonga, Evawani Martalena; Pane, Masdalina (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Occupations related to hospitals or health have a high tendency to be exposed to work stress or depression. Work stress becomes a risk to the health and safety of workers when the work carried out exceeds the capacity, resources and abilities of workers for a long time. This study aims to determine the factors associated with the incidence of stress on doctors at Santa Elisabeth Hospital Medan in 2021. This study used a cross-sectional design. The population in this study were all doctors at the 2021 Hospital, totaling 85 people. The number of samples is 46 people. Data was collected by distributing questionnaires to respondents. Data analysis consisted of univariate analysis, bivariate with Chi Square test, multivariate with Logistic Regression test. The results showed that there was a relationship between workload (p= 0.002; PR = 2.4; 95% CI 1.254 – 4.844), fatigue (p= 0.010; OR = 2.3; 95%CI 1.108-4.870) on the incidence of work stress. to the hospital doctor. While the interaction variables with superiors (p = 0.282; PR = 1.3; 95%CI 0.906-2.077), interaction with coworkers (p = 0.078; PR = 1.6; 95%CI 0.152 – 2.411), job security ( p = 0.516; PR = 1.3; 95% CI 0.829-1.962) on work stress on doctors. The dominant variable related to the incidence of work stress in doctors is the workload variable (p = 0.004; PR = 9.4; 95%CI 2.032-43.854), meaning that doctors who have a high workload have 9.4 times the tendency to experience abnormal stress compared to doctors who have a high workload. with low workload. Thus, it is hoped that the hospital will pay attention to the workload of doctors so that doctors can provide good service and comfort to patients who visit the hospital.